An economic evaluation model of the logistic system based on container transportation - Vasiliauskas, Aidas V.; Barysienė, Jurgita (Transport, 2008)
Over the recent years, the use of containers in the transport system has dramatically increased. The rise of world containerisation is the result of the interplay of macroeconomic, microeconomic and policy‐oriented factors. World trade is facilitated through the elimination of trade barriers and the liberalisation and deregulation of markets. Market liberalisation revealed a demand for enhancing the development of logistics services throughout the world. In the conceptual metamorphosis of the transportation system, cargo movements are viewed in light of the total distribution system. Producers, commodity shippers, ocean, air and land carriers, ports, logistics managers, freight forwarders and consignees are involved in such a total system. The physical distribution of cargo, then, involves an integrated logistics system. This article examines of changes in the transport system that occurred during the last decades because of the invention and application of containers. Moreover, an economic model of evaluating the logistic system based on container transportation is discussed. First published online: 27 Oct 2010